The Panera Bread LBO - Stowell, David (David P.); Katz, Alexander, active 2019 (London : Kellogg School of Management, 2019)
This case considers the buyout of Panera Bread from the perspective of a private equity fund. In early 2017, KLG Managing Director Tom Denning is considering a leveraged buyout of Panera Bread, a rapidly growing fast-casual restaurant company. A surprising Bloomberg News story signals that the deal process is broadening and KLG will have to act quickly if it hopes to buy Panera Bread. Students assume the role of Tom Denning as he prepares an investment recommendation for KLG's investment committee. In doing so, students are required to consider a very large and expensive investment. Students are challenged to create an investment recommendation by performing due diligence, determining additional questions to ask, and pricing a buyout bid that incorporates an optimal capital structure and meets KLG's return requirements. The Panera Bread case is designed to give students insight into the private equity investment process.
Originally Published InStowell, D., & Katz, A. (2019). The Panera Bread LBO. 5-219-250. Evanston, IL: Kellogg School of Management, Northwestern University.
Includes bibliographical references.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Panera Bread (Café) -- Case studies; Leveraged buyouts -- Case studies; Restaurant management -- Case studies